Peta Kekuatan, Kelemahan, Peluang Dan Ancaman (SWOT) Industri Arang Tempurung Kelapa Di Kelurahan Muncul, Tangerang Selatan - Radhita Nurul Paradise; Rima Marisa; Noviana Putri; Cahyaning Dian Utami; Imal Istimal (ITB Ahmad Dahlan Jakarta, 2018)
The coconut shell charcoal can be used as alternative fuel will become more environmentally friendly, easy to obtain, more economical and can be used by the wider community. In South Tangerang city, there are many home industries producing charcoal shell. Thus, this study will analyze the map strengths, weaknesses, opportunities and threats of the home industry. The results of the analysis using SWOT matrix shows that this industry has a very strategic position to be developed. Policy recommendations of the result is the industry needs to cooperate with coconut farmers and sellers of coconut in the traditional market, so supply remains awake.